PLATONO OLOS DEKONSTRUKCIJA. - Jankauskas, Skirmantas (Problems / Problemos, 2011)
The paper discusses perhaps the most exploited and often misinterpreted construct in the tradition of philosophy -- Plato's allegory of cave. At the beginning, stylized analytical and poetic interpretations of the construct are presented and their polemic points are highlighted. Further, the singular features of the knowing subject of the Greek philosophizing, namely, of the soul are identified. It is said that, otherwise than the post-descartian cogito, the soul is ethically constituted and existentially engaged and presupposes an uninterrupted linkage between mind and senses. The paper focuses on the analogy of line that precedes the allegory of cave and, on its turn, details the statement of Plato about the role of good in constituting the being and its knowing. The analogy of line is explicated taking into account the singular features of the knowing subject of the Greek philosophizing. Two specific circumstances characteristic to Plato's philosophizing -- his ardent polemical attitude towards sophists and his predilection to mathematics -- are taken into account as well. The exclusiveness of Plato's thinking is revealed by contrasting it with the simplifying ideas of Aristotle and the deconstructive attitude of Descartes' cogito. Finally, the considerations are summarized in the article in a particular way by citing an excerpt from a famous poem of Lithuanian poet.